2017
DOI: 10.1007/s00431-017-2958-0
|View full text |Cite
|
Sign up to set email alerts
|

Seizure disorders and developmental disorders: impact on life of affected families—a structured interview

Abstract: Parents perceive changes in their daily life and discrimination of their children due to their children's seizure and developmental disorders. An intellectual disability combined with seizure disorder caused the highest constraint. What is Known: • Seizure and/or developmental disorders of children may adversely influence quality of life for affected parents. • Caring for a child with special health care needs can take complete attention and own parental needs may therefore be difficult to meet. What is New: •… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 28 publications
1
26
1
1
Order By: Relevance
“…[10,11,17] Comorbid conditions may also contribute to caregiver burden and impaired QoL as the caregiver may devote more time, energy, and i nancial resources to the care of the patient. [24,25,33] Nevertheless, in the present study, younger age, treatment duration >5 years, polytherapy and comorbidities were not signii cantly associated with caregiver burden. A larger sample of participants may help draw more conclusive evidence to prove this association among Filipino patients.…”
Section: Caregiver Burden and Qol Of Caregiverscontrasting
confidence: 69%
See 2 more Smart Citations
“…[10,11,17] Comorbid conditions may also contribute to caregiver burden and impaired QoL as the caregiver may devote more time, energy, and i nancial resources to the care of the patient. [24,25,33] Nevertheless, in the present study, younger age, treatment duration >5 years, polytherapy and comorbidities were not signii cantly associated with caregiver burden. A larger sample of participants may help draw more conclusive evidence to prove this association among Filipino patients.…”
Section: Caregiver Burden and Qol Of Caregiverscontrasting
confidence: 69%
“…They may even develop prejudice, negative attitude, and psychological distress like depression and anxiety. [24] When seizure is associated with developmental disorder, parents report more constraints compared to those with seizure alone. [24] Furthermore, these children with developmental disorders may become dependent life-long upon their caregivers, hence the caregiving process does not decrease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epilepsy can have a negative impact on the quality of life of children and adolescents that can be aggravated by a developmental disorder and further aggravated by ADEs [24]. The results of the present study showed a high burden of experienced ADEs with a negative impact especially on the emotional situation, on school performance, and on favorite leisure activities.…”
Section: Burden Of Experienced Adesmentioning
confidence: 47%
“…Several studies have explored the extent of knowledge and experiences regarding these issues. These have focussed on teachers (Dumeier et al, 2015;2017a;2017b), parents (Lewis et al, 2010;Bertsche et al, 2013;Spindler et al, 2017), patients (Lewis et al, 2010;Bertsche et al, 2013;Spindler et al, 2017), patients (Lewis et al, 2010;Pauschek et al, 2016;Kadel et al, 2018), or the public (Fong and Hung, 2002;Kartal and Akyıldız, 2016;Jansen et al, 2017). A recent study investigated the educational needs of physicians working in paediatric epileptology with emphasis on neurologists and neuropaediatricians (Murray et al, 2018).…”
mentioning
confidence: 99%